2023
DOI: 10.1177/13623613231171980
|View full text |Cite
|
Sign up to set email alerts
|

Motor deficits in autism differ from that of developmental coordination disorder

Abstract: Autism spectrum disorders and developmental coordination disorders are both associated with sensorimotor impairments, yet their nature and specificity remain unknown. In order to clearly distinguish the specificity between the two disorders, children with autism spectrum disorder or developmental coordination disorder presenting the same degree of motor impairment, thus homogeneous profiles, were examined in a reach-to-displace paradigm, which allows the integrity of two main aspects of motor control (anticipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…Researchers have also used infrared motor capture technology to look at movement kinematics of different motor patterns. Martel et al (2023) examined the motor control during a reach-to-displace paradigm, where the weight of an object was either known or unknown. Using this paradigm, Martel et al (2023) found evidence of impaired feedforward control, where autistic children appeared to rely on somatosensory information to inform their subsequent movements.…”
Section: Overview Of Updates In Music/rhythm For Sensorimotor Organiz...mentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have also used infrared motor capture technology to look at movement kinematics of different motor patterns. Martel et al (2023) examined the motor control during a reach-to-displace paradigm, where the weight of an object was either known or unknown. Using this paradigm, Martel et al (2023) found evidence of impaired feedforward control, where autistic children appeared to rely on somatosensory information to inform their subsequent movements.…”
Section: Overview Of Updates In Music/rhythm For Sensorimotor Organiz...mentioning
confidence: 99%
“… Martel et al (2023) examined the motor control during a reach-to-displace paradigm, where the weight of an object was either known or unknown. Using this paradigm, Martel et al (2023) found evidence of impaired feedforward control, where autistic children appeared to rely on somatosensory information to inform their subsequent movements. Conversely, Arthur et al (2020) used infrared movement kinematics technology and gaze data to test prediction-related sensorimotor control.…”
Section: Overview Of Updates In Music/rhythm For Sensorimotor Organiz...mentioning
confidence: 99%